Strategi Driver Grab Surabaya Dalam Meningkatkan Kesejahteraan Ekonomi Pada Masa Pandemi Covid - Judhistira, Prima Rizky; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2022)
The purpose of this study is to find out the strategies used by Grab drivers in Surabaya in increasing income and welfare during the Covid-19 pandemic and to find out the strategies carried out from an Islamic perspective. The approach taken uses a qualitative approach. The variables used are the driver grab strategy and the improvement of economic welfare. The population used is the grab driver who is in Surabaya by using an interview approach and recording the results of the interview. The data used are primary and secondary data types. Primary data was obtained by conducting direct interviews with informants, and secondary data obtained from online media. The results of this study indicate that strategies such as moving places, making good use of operating hours, offering promotions, providing the best service and maximizing existing incentives can improve welfare and nothing deviates from Islamic teachings. All strategies carried out do not harm any party and are allowed in Islam, the income of Surabaya grab drivers has also increased after using their respective strategies.